PAIN REDUCTION AFTER WET AND DRY CUPPING THERAPIES: ROLES OF α2β1 INTEGRIN AND μ-OPIOID RECEPTOR IN ANIMAL MODELS - Subadi, Imam; BoyaNugraha,; AbdulhadiSuwandi,; Sulastri, Nur; Susilo, Imam (International Journal of Psychosocial Rehabilitation, 2020)
Background: Wet cupping therapy (WCT) and dry cupping therapy (DCT) are complementary therapies in pain management. Stretching keratinocytes by cupping seems to stimulate the expression of α2β1-integrin. Its benefit in pain reduction could be mediated by the expression of the μ-opioid receptor (MOR). Objective: This study aims to determine pain thresholds, α2β1-integrin, and MOR after WCT and DCT. Method: Thirty-two adult male Wistar rats were divided into negative control, positive control, DCT, and WCT groups. In the DCT group and WCT group, cupping was conducted at the left and right paralumbar regions 48 hours after CFA injection. A hot plate test was conducted 24 hours after therapy to assess pain threshold, and immunohistochemistry was conducted from the skin for α2β1-integrin and the spinal cord for MOR. Result: WCG showed the highest expression of α2β1-integrin in the keratinocytes and MOR in the lamina II spinal cord than the other groups. On immunohistochemical examination, the expression of α2β1 integrin showed positive cells (keratinocytes) with brown stain on dry cupping and wet cupping. Significant differences were shown between the negative control group and the positive control group, dry cupping therapy group, and wet cupping therapy group. Conclusion: WCT is more effective than DCT in reducing pain. The benefit of both therapies in reducing pain in rats could be mediated by the expression of α2β1-integrin and MOR.